Selective migration of population in functional urban regions of Slovakia - Loránt Pregi; Ladislav Novotný (Journal of Maps, 2019)
Majority of research on urban development perceive migration as internally homogeneous phenomenon that influences growth and spatial redistribution of population. This enables to identify certain general migration patterns, but understanding regularities and consequences requires looking at internal structure of migration. This paper aims to visualise the impact of selective migration to the population structures across multiple spatial scales and in a complex way taking Slovakia as the case study. By this means spatial patterns of migration are demonstrated in a more efficient way. The resulting maps show the impact of migration is selective at various spatial levels regarding age and educational attainment. In comparison with general migration, selective migration shows stronger spatial polarisation in Slovakia.